Structural and Biochemical Insights into Bis(2-hydroxyethyl) Terephthalate Degrading Carboxylesterase Isolated from Psychrotrophic Bacterium Exiguobacterium antarcticum - Jisub Hwang; Wanki Yoo; Seung Chul Shin; Kyeong Kyu Kim; Han-Woo Kim; Hackwon Do; Jun Hyuck Lee (International Journal of Molecular Sciences, 2023)
This study aimed to elucidate the crystal structure and biochemically characterize the carboxylesterase EaEst2, a thermotolerant biocatalyst derived from Exiguobacterium antarcticum, a psychrotrophic bacterium. Sequence and phylogenetic analyses showed that EaEst2 belongs to the Family XIII group of carboxylesterases. EaEst2 has a broad range of substrate specificities for short-chain p-nitrophenyl (pNP) esters, 1-naphthyl acetate (1-NA), and 1-naphthyl butyrate (1-NB). Its optimal pH is 7.0, losing its enzymatic activity at temperatures above 50 °C. EaEst2 showed degradation activity toward bis(2-hydroxyethyl) terephthalate (BHET), a polyethylene terephthalate degradation intermediate. We determined the crystal structure of EaEst2 at a 1.74 Å resolution in the ligand-free form to investigate BHET degradation at a molecular level. Finally, the biochemical stability and immobilization of a crosslinked enzyme aggregate (CLEA) were assessed to examine its potential for industrial application. Overall, the structural and biochemical characterization of EaEst2 demonstrates its industrial potency as a biocatalyst.